Ecodrainage Model to Handle the Inundations in the City Center of Demak - Risa Niken R. T. H.; S. Imam Wahyudi; Hermin Poejiastoeti (Universitas Islam Sultan Agung, 2019)
The growth and development of the city is strongly influenced by an increase in population in line with the increasing demand for space and land. On the other hand, the availability of urban land is very limited, resulting in the conversion of land use to meet those needs. It is necessary to change the paradigm of the concept of a conventional drainage system to the concept of an environmentally friendly drainage system (ecodrainage). The ecodrainage concept is expected to be an effort to deal with inundation and groundwater conservation in city center of Demak. The quantity of the rainwater infiltration wells (RIW) was obtained based on the analysis to reduce the inundation in the city center of Demak. With the reference to the rainfall repetition period (RRP) of 2 years, 21 units of the well were needed to accommodate the rainwater runoff discharges of 0.878 m3/s. Due to the land limits at the area of research, only could 20 units of the well be constructed, as a result, it could only reduce the inundation by 0.811 m3/s or 90.48 %. Considering the rainfall repetition period (RRP) of 5 years, around 40 units of rainwater infiltration wells (RIW) were needed to accommodate the rainwater runoff discharge of 1.70 m3/s, yet only could 35 out of 40 wells as required be constructed, consequently, it was only able to reduce the inundation of 1.494 m3/s or 87.50.